Analisis Struktur Morfologi Dan Gugus Fungsi Serbuk Kopi Robusta Toraja - Ishak Pawarangan; Dwi Prasetyawati Thana; Wilson Jefriyanto; Eko Suripto Pasinggi; Rali Sarira Bone; Yosep Mari'; Conny Conny (Jurnal Kimia Fullerene, 2023)
Coffee is one of the most popular beverages in the world. The purpose of this research is to examine the morphological structure and composition of Toraja Robusta coffee. Scanning Electron Microscopy (SEM) was used to analyze the morphological structure and elemental analysis of Robusta coffee powder, as well as functional group analysis using Fourier transform infrared spectroscopy (FTIR). Microscopic examination reveals that the surface of Toraja Robusta coffee grounds is uneven. Furthermore, the elements Carbon, Oxygen, Nitrogen, Potassium, and Magnesium were discovered in Toraja Robusta coffee powder. Furthermore, functional group analysis results show that Toraja Robusta coffee powder has several functional groups at various wave numbers. This research advances our understanding of the morphological structure and composition of Toraja Robusta coffee powder, which can be used as a reference in coffee processing and marketing. Furthermore, the findings of this study can help improve the quality and selling value of Toraja Robusta coffee as a local Indonesian coffee product that is distinct and distinct from other types of coffee.